Analysis Of Factors Affecting The Auditor's Opinion - Ivica Filipović (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
The auditor's opinion is the key message of every audit report. The audit report is the main product of the engagement of external auditors. Through this engagement, the members of the audit team try to form a conclusion on whether the client's financial statements, which are the subject of an external audit, have been created in accordance with the applicable financial reporting framework. The conclusion formed regarding truthfulness of presented financial statements is presented in a special section of the auditor's report - the auditor's opinion. That section, which contains the auditor's opinion, is a kind of seal of independent external auditors' engagement. Namely, the expressed auditor's opinion is a support for many users of information from financial statements for making business decisions. Precisely because of the importance of the auditor's opinion in business decision-making, space is opened for analyzing various factors that can influence that opinion. For the purposes of this research, the following factors were analyzed, among others: indebtedness, classification of the audit firm in the "Big Four", rotation of the audit firm and return on assets (ROA). In this regard, a model suitable for such research was designed and its testing was carried out on companies listed on the Zagreb Stock Exchange in the Republic of Croatia.